Open-Loop Control of Electrically Conductive Materials in an Oscillating Magnetic Field - Stewart, Seth; Pawelski, Joseph; Ward, Steve; Petruska, Andrew J. (IEEE transactions on robotics, 2025)
Control of objects using remotely generated magnetic fields has established itself as a viable option for 3-D position control, though the objects being manipulated to date have largely been limited to soft and hard-magnetic objects that react to a static magnetic field. This limits the application to a small subset of materials. This work presents the first analytically derived model for 3-D position control of any electrically conductive material subject to a time-varying magnetic field. By leveraging the induced eddy current and subsequent induced dipole, this model shows that conductive materials behave equivalently to diamagnetic materials and are, therefore, not subject to the limitations of the Earnshaw's theorem, making stable, open-loop levitation possible. This is demonstrated by open-loop position control of a semibuoyant aluminum sphere.